2016
DOI: 10.1186/s12935-016-0338-x
|View full text |Cite
|
Sign up to set email alerts
|

High EZH2 expression is correlated to metastatic disease in pediatric soft tissue sarcomas

Abstract: BackgroundEnhancer of Zeste Drosophila Homologue 2 (EZH2) is a key regulator of transcription as a member of polycomb repressive complex 2 (PRC2) which exerts repression of downstream genes and is correlated to invasiveness and progression of different tumours. Therefore, we evaluated the expression of PRC2 proteins in pediatric soft tissue sarcoma (rhabdomyosarcoma, RMS and extraosseous Ewing sarcoma, EES) correlating them to the clinical outcome of the patients.MethodsWe analyzed PRC2 protein expression by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…Further studies are needed to ensure that it does not interfere with other vital molecular processes . Ramaglia and colleagues suggested approaching with caution to possible extensive usage of DZNep in myeloid neoplasms, also stressing the importance of additional studies . A common theme between other inhibitors is the pyridine group .…”
Section: Prc2 and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to ensure that it does not interfere with other vital molecular processes . Ramaglia and colleagues suggested approaching with caution to possible extensive usage of DZNep in myeloid neoplasms, also stressing the importance of additional studies . A common theme between other inhibitors is the pyridine group .…”
Section: Prc2 and Cancermentioning
confidence: 99%
“…The molecular mechanisms that cause the overexpression of EZH2, and the malignant effects that accompany it are also important for evaluating potential biomarkers. Proteins such as EWS/FL11, E2F1, and MYC have all been shown to induce EZH2 expression while cyclin‐dependent kinase 1/2 has been shown to stimulate it . One study shows that the long coding RNA ROR1‐AS1 interacts with the PRC2 complex through the EZH2 protein and that inhibition of EZH2 abolishes this interaction.…”
Section: Prc2 and Cancermentioning
confidence: 99%
“…Ewing sarcoma and RMS are common pediatric sarcomas with high malignance. Ramaglia 10 found that EZH2 was expressed with a different degree in 60% of 17 patients with Ewing sarcoma or RMS and it was significantly higher in patients presenting lymph node and/or distant metastases. Moreover, overexpression of EZH2 was positively relative to lower probability of survival.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Recent studies have shown that, in both ERMS and ARMS, epigenetic dysregulation plays a role in inhibition of terminal myogenic differentiation, and in promotion of proliferative, invasive, and metastatic phenotypes. [4][5][6][7] Genome-wide profiling of DNA methylation in RMS has shown that, while there are common epigenetic aberrations among ERMS and ARMS, they also have distinct epigenetic profiles. [8][9][10] Specifically, fusion-positive (ARMS) tumors showed global decreased methylation when compared to ERMS tumors, with higher frequency of CpG sites that had low methylation, and a lower frequency of CpG that had higher methylation levels.…”
Section: Introductionmentioning
confidence: 99%